Design and fabrication waste collector prototype / Muhammad Faiszam Isnin - Muhammad Faiszam, Isnin (2022)
In this era, rivers are an important aspect in an ecosystem. This is because rivers are the main source for humans to get clean water. Despite environmental regulations that protect the quality of the river, solid waste in the form of trash, litter and garbage often ends up in these surface waters. Currently, over 23,000 tonnes of waste are produced each day in Malaysia. However, this amount is expected to rise to 30,000 tonnes by the year 2020. The amount of solid waste generated continues to increase due to the increasing population and development and only less of the solid waste is being recycled. A clean environment is the basic life supporting system and pure water plays a prominent role in balancing the ecosystem. Therefore, this study identifies to overcome the increase of solid waste in a river by the construction of a waste collector prototype. In addition, this prototype will significantly contribute since the solid wastes will flow in the same direction as current of a river